Perceptions of COVID-19-related risk and mortality among ethnically diverse healthcare professionals in the UK. Issue 1 (2nd January 2021) - Ali, Parveen; Adam, Zulfiquar; West, John; Pareek, Manish; Raza, Muhammad; Iqbal, Javaid
ABSTRACT: Background: A number of Healthcare Practitioners (HCPs), mostly from Black, Asian and minority ethnic (BAME) origin have died with COVID-19. This survey aimed to explore the views of an ethnically diverse sample of HCPs in the UK about COVID-19-related deaths among HCPs in general and BAME HCPs in particular. Methods: It is a cross-sectional prospective survey of HCPs in UK and was conducted online using Google Forms between 28th April and 4th May 2020. Findings: A total of 1119 UK HCPs (aged 45.0 ± 9.5 years, 56% males, 71% BAME) participated. Seventy-two per cent of respondents reported being worried about COVID-19 and 84% had concerns about personal protective equipment (PPE). Almost all (93%) respondents felt that inadequate PPE may be a contributory factor to HCP deaths. Half of the respondents, especially younger and BAME, reported feeling unable to say 'no', if asked to work without adequate PPE. BAME HCPs were considered at a higher-risk of acquiring coronavirus and dying with COVID-19. Reasons for excess BAME HCP deaths were believed to be comorbidities, inadequate PPE and working in high-risk areas. Majority (81%) of respondents felt that the government has been slow to respond to COVID-19 related deaths in HCPs and 67% HCPs were of the opinion that BAME workers with risk factors should be removed from direct clinical care. Interpretation: HCPs have significant COVID-19-related concerns. BAME HCPs are considered at increased risk due to comorbidities, working in high-risk areas, and inadequate PPE. BAME HCP should have a thorough risk assessment and high-risk HCPs may need work adjustment or redeployment. All HCPs must have appropriate training and provision of PPE.